2020
DOI: 10.1097/dss.0000000000002648
|View full text |Cite
|
Sign up to set email alerts
|

Variables Affecting Basal Cell Carcinoma and Melanoma In Situ Excision Clearance: A Multi-institutional Retrospective Study

Abstract: BACKGROUND The primary endpoint for surgical excision of skin cancer is the positive margin status. Tumor characteristics may explain much of this risk, but other important factors can include physician specialty. OBJECTIVE To determine the variables affecting the success of a basal cell carcinoma (BCC) or melanoma in situ (MIS) excision. METHODS/MATERIALS An 8-year, multicenter, retrospective study of 5,800… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
2
2
0
Order By: Relevance
“…Furthermore, there was no difference in median tumour size between incompletely and completely excised tumours. These results are in line with previous studies where the same conclusion was reached ( 13 , 14 , 25 ). Nevertheless, these studies included all histopathological subtypes of BCCs.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Furthermore, there was no difference in median tumour size between incompletely and completely excised tumours. These results are in line with previous studies where the same conclusion was reached ( 13 , 14 , 25 ). Nevertheless, these studies included all histopathological subtypes of BCCs.…”
Section: Discussionsupporting
confidence: 93%
“…The tumours of general surgeons and general practitioners were localized only on the face and scalp in 2% ( n = 2) and 18% ( n = 14) of cases, respectively, so it was deemed irrelevant to further analyse IERs for these physician specialties. Consistent results with no significant differences in IERs between different physician specialties have been observed in some studies ( 25 , 35 ). Although a few studies have shown that dermatologists have lower IERs than other physician specialties ( 11 , 17 ), the relevance of physician specialty when looking at IERs of aggressive BCC subtypes on the face and scalp is probably limited or non-existent and highly affected by confounding factors.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations